2022
DOI: 10.1007/s40618-022-01742-5
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue in COVID-19: detection of SARS-CoV-2 in adipocytes and activation of the interferon-alpha response

Abstract: Objective Obesity is a recognized risk factor for the progression to severe forms of COVID-19, yet the mechanisms of the association are unclear. Methods Subcutaneous abdominal adipose tissue specimens of subjects deceased from COVID-19 (n = 23) were compared to those of controls dying abruptly from causes other than infectious (accidental trauma, sudden cardiac death). Alterations of lung parenchyma consistent with moderate to severe disease were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 49 publications
(33 reference statements)
4
32
0
2
Order By: Relevance
“…Although we show infection of adipocytes with SARS-CoV-2, we were surprised that we did not detect corresponding expression of ACE2 , the canonical SARS-CoV-2 entry receptor, in fresh adipose tissue. Prior reports of ACE2 RNA expression in whole adipose tissue relied primarily on bulk transcriptomic approaches and suggested that ACE2 expression could be influenced by factors including diet, obesity, and COVID-19 ( 23 , 24 , 90 92 ). In freshly isolated mature adipocytes, we only sporadically detected ACE2 RNA, whereas it was consistently identified in differentiated preadipocytes, consistent with another recent report ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although we show infection of adipocytes with SARS-CoV-2, we were surprised that we did not detect corresponding expression of ACE2 , the canonical SARS-CoV-2 entry receptor, in fresh adipose tissue. Prior reports of ACE2 RNA expression in whole adipose tissue relied primarily on bulk transcriptomic approaches and suggested that ACE2 expression could be influenced by factors including diet, obesity, and COVID-19 ( 23 , 24 , 90 92 ). In freshly isolated mature adipocytes, we only sporadically detected ACE2 RNA, whereas it was consistently identified in differentiated preadipocytes, consistent with another recent report ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…A third suggestion is that increased angiotensin-converting enzyme (ACE2) expression in adipose tissue of obese individuals could make it a vulnerable target for COVID-19 infection, especially given the higher expression of ACE2 in adipocytes, compared to lung tissue [34] , [35] . Evidence that SARS-CoV-2 can directly infect adipocytes [36] supports the hypothesis that adipose tissue represents an important viral reservoir for increased viral shedding [37] , [38] . This had previously been reported in studies on influenza, with elevated viral loads in exhaled breath, prolonged viral shedding, and obesogenic environments favouring the emergence of novel, more virulent virus strains [39] , [40] , [41] .…”
Section: Healthy Weight Maintenancementioning
confidence: 80%
“…The presence of SARS-CoV-2 in the adipocytes of fat from COVID-19 patients has been demonstrated in a very recent paper that also showed chronic inflammation with upregulation of the interferon-alpha pathway [50]. Of note, interferon-alpha stimulates the expression of ACE2 and this type of condition has been reported in chronic lung diseases that appear to stimulate gene expression programs promoting both the cellular entry of SARS-CoV-2 and the severity of COVID-19 [51].…”
Section: Covid-19 and The Obese Adipose Organmentioning
confidence: 84%